2015
DOI: 10.1162/rest_a_00433
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Stability of Time Preferences

Abstract: The preferences assumed to govern intertemporal trade-offs are generally considered to be stable economic primitives, though evidence on this stability is notably lacking. We present evidence from a large field study conducted over two years, with around 1,400 individuals using incentivized intertemporal choice experiments. Aggregate choice profiles and corresponding estimates of discount parameters are unchanged over the two years and individual correlations through time are high by existing standards. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
144
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(168 citation statements)
references
References 50 publications
20
144
2
2
Order By: Relevance
“…Indeed, it has been shown that personal experiences and time-varying attributes can affect risk attitudes and risk taking (e.g., Malmendier and Nagel 2011;Sahm 2012). We do not attempt such a decomposition of m t here, in part because previous work has shown that changes in observables can explain only a small share of the transitory variation in measured preferences (Andersen et al 2008;Josef et al 2016;Meier and Sprenger 2010;Sahm 2012), and in part because only about a year elapsed on average between the first and the second measurements. Also, though previous work (e.g., Choi et al 2014;Dave et al 2010;von Gaudecker et al 2011) has shown the consistency or variance of decision-making under uncertainty is related to socio-economic characteristics, we do not model m t as dependent on covariates, as this would add a significant layer of complexity to the model and estimation and is not of direct relevance for the objectives of this paper.…”
Section: Summary Statisticsmentioning
confidence: 99%
“…Indeed, it has been shown that personal experiences and time-varying attributes can affect risk attitudes and risk taking (e.g., Malmendier and Nagel 2011;Sahm 2012). We do not attempt such a decomposition of m t here, in part because previous work has shown that changes in observables can explain only a small share of the transitory variation in measured preferences (Andersen et al 2008;Josef et al 2016;Meier and Sprenger 2010;Sahm 2012), and in part because only about a year elapsed on average between the first and the second measurements. Also, though previous work (e.g., Choi et al 2014;Dave et al 2010;von Gaudecker et al 2011) has shown the consistency or variance of decision-making under uncertainty is related to socio-economic characteristics, we do not model m t as dependent on covariates, as this would add a significant layer of complexity to the model and estimation and is not of direct relevance for the objectives of this paper.…”
Section: Summary Statisticsmentioning
confidence: 99%
“…Several studies (for example Meier and Sprenger, 2015;Chuang and Schechter, 2015;Halevy, 2015;Janssens, Kramer, and Swart, 2017) estimate discount rates using experimental windfalls for the same indi-viduals at different points in time. Time preferences vary over time, in part due to random noise in decision making and in part due to liquidity constraints.…”
Section: Introductionmentioning
confidence: 99%
“…Dohmen et al (2011) shows that risk aversion is relatively stable in different contexts. For evidence on temporal stability of time preference, see Meier and Sprenger (2015).…”
mentioning
confidence: 99%